Law, Humanities and the COVID Crisis - Stychin, Carl F. (University of London Press, 2023)
While there has been an abundance of scientific works on the COVID-19 crisis, there has been relatively little research to date from the humanities. This striking new book seeks to address the immediacy of COVID-19 by focusing on the implications of the virus in a wider interdisciplinary context - through the lens of the law, history, ethics, technology, economics and gender studies.From Europe to South America, Asia and beyond, Law, Humanities and the COVID Crisis sets out a framework for understanding the COVID-19 virus beyond its epidemiological constraints, asking us to question the very definition of what it means to be human. Researchers from around the world offer their critical reflections on the past, present, and future of this period of sociocultural upheaval and the tremendous suffering that has laid bare fundamental imbalances in our society. Featuring essays on public welfare versus private interest, violence against women, mask compliance, conspiracy theories and national security laws, this book is a significant contribution to understanding our new 'post-COVID' landscape, and the future yet to come.